Honeybees: The Pollinator Sustaining Crop Diversity - Shrestha, Jagadish Bhakta (Journal of Agriculture and Environment, 2009)
Importance of honeybees as prime pollinators for continual maintenence of crop-diversity and need of their conservation for sustainable agriculture is highlighted based on literature review. Somatic, reproductive and adaptive heterosis or hybrid effects that occur in plant progeny as a result of natural cross-pollination by honeybees brings about significant qualitative and quantitative changes in the economic and biological characteristics of crop plants. Honeybees often facilitate genetic enrichment of native plants through crosspollination offering to their varietal development and adaptation in the changing environment. The natural environment is required to provide bees with habitat or nesting sites. Promotion of organic farming and integrated pest management programs are necessitated. Keywords: Eco-system; Honeybees; Pollinators; Cross-pollination; Sustainable agriculture The Journal of Agriculture and Environment Vol:.9, Jun. 2008 Page: 90-92